Profitabilitas Memoderasi Pengaruh Likuiditas, Leverage dan Operating Capacity Terhadap Financial Distress (Profitability Moderates the Effect of Liquidity, Leverage and Operating Capacity on Financial Distress) - Pebrianti, Grestika; Suryadi, Edy; Safitri, Heni (STIE Malangkucecwara, 2023)
This study aims to determine the role of Profitability (ROA) moderates the effect of Liquidity (CR), Leverage (DER), and Operating Capacity (TATO) on Financial Distress, with a research focus on service companies in the tourism subsector, restaurants, hotels, and transportation companies listed on the Indonesia Stock Exchange for the 2019-2021 period. A sample of 55 companies was used which was taken by purposive sampling technique. Quantitative research method with causal research used in this study, with moderated regression analysis (MRA) as the analytical tool. This analysis results that CR has a partial effect on financial distress, while DER and TATO have no effect. In addition, this study found no evidence to suggest that ROA can moderate the correlation between CR, DER, and TATO in financial distress.